N-[4-(3-methyl-3-mesityl-cyclobutyl)-thiazol-2-yl]-succinamic acid: X-ray structure, spectroscopic characterization and quantum chemical computational studies (vol 1046c, pg 1, 2013) - Sen, Fatih; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Elsevier, 2013)
[Abstract Not Available]